VALIDITAS PERMAINAN CONGKLAK PADA MATERI TATA SURYA UNTUK SISWA SMP KELAS VII - Luvi Festy Zarafayana; Laily Rosdiana (PENSA: E-JURNAL PENDIDIKAN SAINS, 2020)
The research carried out aims to describe the validity of the Congklak game on solar system material for seventh grade junior high school students. This research was conducted at SMPN 2 Pungging with a total of 24 students. This research is a development research that is using the ADDIE development model. The resulting data instrument was in the form of a study sheet and a validation sheet. The results of the research on the validity of the Congklak game can be reviewed from the results of the validation sheet and the study sheet that has been filled in by expert lecturers and science subject teachers. Analysis of the results on the validation sheet is obtained an average mode value of 4. The conclusion of this study is the validity of the developed Congklak game consists of several aspects namely the content aspect, linguistic aspects, media presentation aspects, and aspects of the game function get a very decent category used with a feasibility mode value of 4.